2019
DOI: 10.1002/er.4514
|View full text |Cite
|
Sign up to set email alerts
|

Production of butanol and polyhydroxyalkanoate from industrial waste byClostridium beijerinckiiASU10

Abstract: Summary This study demonstrated a biotechnological approach for simultaneous production of low‐cost H2, liquid biofuels, and polyhydroxyalkanoates (PHAs) by solventogenic bacterium (Clostridium beijerinckii) from renewable industrial wastes such as molasses and crude glycerol. C beijerinckii ASU10 (KF372577) exhibited considerable performance for hydrogen production of 5.1 ± 0.84 and 11 ± 0.44 mL H2 h−1 on glycerol and sugarcane molasses, respectively. The total acetone‐butanol‐ethanol (ABE) generation from gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 88 publications
(129 reference statements)
0
14
0
Order By: Relevance
“…In recent decades, due to the alarming increase in motorization, industrialization and human population; mankind faces the inevitable depletion in global strategic petroleum reserves on earth 1 , 2 . As well as the rapid increase in petroleum prices and alarming environmental crises makes bioenergy production from renewable raw materials is considered a sustainable alternative energy source for the future 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, due to the alarming increase in motorization, industrialization and human population; mankind faces the inevitable depletion in global strategic petroleum reserves on earth 1 , 2 . As well as the rapid increase in petroleum prices and alarming environmental crises makes bioenergy production from renewable raw materials is considered a sustainable alternative energy source for the future 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides homopolymers, some microorganisms were found to be able to synthesize scl-mcl-PHA copolymers using molasses as the only carbon source. Hassan et al [ 70 ] observed that Clostridium beijerinckii ASU10 (KF372577) has the potential to produce P(3HB-co-3HO) in the amount of 37.93% of CDW. Gas chromatography–mass spectrometry (GC-MS) analysis confirmed that the extracted copolymer consisted of 47.3 mol% of 3HB and 52.7% of 3HO.…”
Section: Molasses As a Carbon Source For Pha Productionmentioning
confidence: 99%
“…2 In addition to large quantities of total sugars, molasses is also a source of nitrogen and vitamins. 3 Thus, molasses is a cheap carbohydrate that can be used as a resource on the fermentative generation of butyrate, 3 butanol, 4 hydrogen, [5][6][7][8][9] and succinate. 10 Succinic acid is generated as an intermediate metabolite in the tricarboxylic metabolite cycle.…”
Section: Introductionmentioning
confidence: 99%